Neurociencias y Ejercicio como Pilares Fundamentales de la Salud Física y Mental en Oaxaca México - Jesús Cristian Esponda Martínez; Emanuel de Jesús Cortés Santiago; Carlos Augusto López Ramírez; Virgilio Ortega García; Luis Abel Solano Santiago (Ibero Ciencias - Revista Científica y Académica - ISSN 3072-7197, 2026)
This study analyzes the role of physical exercise in modulating the neurobiological mechanisms that underlie mental and physical health, emphasizing its analogical transferability to the population profile of the state of Oaxaca. Consolidated evidence demonstrates that aerobic training, combined with resistance exercise, increases brain-derived neurotrophic factor concentrations. Furthermore, it elevates hippocampal volume by 1% to 2%, enhances prefrontal-amygdala functional connectivity, and attenuates both hypothalamic-pituitary-adrenal axis reactivity and systemic inflammation, yielding clinically significant effects on anxiety, depression, and executive functions. These universal processes coexist, within the Oaxacan context, with a structural paradox characterized by 90% incidental physical activity, high metabolic comorbidity, along with a probable underreporting of mental health conditions. This research synthesizes the available scientific literature, both national and international, through a conceptual model useful for informing public policy recommendations with a gender perspective, intersectionality, as well as early detection strategies. The core of the manuscript lies in defining the boundaries between incidental physical activity and structured exercise, providing direct implications for designing interventions that optimize the motor substrate, in addition to the preexisting lifestyle of the Oaxacan population